Doping Ag Terhadap Sintesis Nanopartikel ZnO Menggunakan Metode Sol-Gel Untuk Meningkatkan Efisiensi Sel Surya - Putra, A.A. Made Wisnu Wijaya; Giriantari, I.A.D.; Setiawan, I.N. (Majalah Ilmiah Teknologi Elektro; Vol 23 No 2 (2024): (Juli - Desember) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2024.v23i02.P02, 2024)
Energy availability is decreasing along with the increasing demand for energy, so renewable energy sources are needed that are environmentally friendly and easily accessible. Dye-Sensitized Solar Cell (DSSC) is one of the environmentally friendly technologies that can be relied on to convert solar energy into electrical energy. In this study, ZnO nanoparticles are being synthesized by adding Ag doping using the sol-gel method. The synthesis process is being carried out by calcination at 600° C for 3 hours and sintering at 850º C for 10 hours. The results of the synthesis are being characterized using X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). Characterization of X-Ray Diffraction (XRD) shows a decrease in the value of the volume fraction due to the addition of Ag doping, where the volume fraction obtained is 71.9%. The particle size obtained is 576.2 nm. The addition of Ag doping does not affect the parameters of the sample grid much, because the magnitude of the values is almost the same, namely a = 3.234083 Å, b = 3.234083 Å, c = 5.194726 Å. In the analysis of the results of Scanning Electron Microscopy (SEM) characterization, the average particle size obtained is 1706.55254 nm. Current and voltage measurements from DSSC with ZnO semiconductors show a current of 14 mA and the voltage produced is 0.22 V. From this data, the efficiency of DSSC with ZnO semiconductors is obtained by 0.29%.